Behaviour of steel fibre reinforced concrete under cyclic compressive loading - Shukla, Mukesh; Choubey, U. B. (2006)
An experimental study was carried out to investigate the behaviour of steel fibre reinforced concrete under cyclic compressive loading. Cylindrical specimens containing two volume fractions (one percent and two percent) of steel fibres and plain concrete specimens were tested under uniaxial monotonic and cyclic compressive loading to establish the stress-strain envelope curve, locus of common points and stability points. An analytical expression is established to represent these curves for SFRC. It was also observed that the permissible stress level depends on the plastic strain present in the material. The plastic strain curves are presented and a general form of second order equation is proposed to represent these curves.